Application of the STAD-type Cooperative Learning Model in Improving Natural Science Learning Outcomes - Muhamad Fahmi Syuhada; Tobroni Tobroni; Rasilah Rasilah; Dede Hadiansah (Journal of General Education and Humanities, 2025)
This study aimed to improve the learning outcomes of fourth-grade students at State Elementary School 1 Singakerta in understanding the characteristics of light through the implementation of the STAD-type cooperative learning model. The research employed a Classroom Action Research (CAR) approach conducted in two cycles with 30 students as participants. Data were collected using tests, observations, and documentation and then analyzed descriptively using qualitative methods. The results revealed a significant improvement in student learning outcomes. The percentage of students achieving the Minimum Mastery Criteria (KKM) increased from 40% in the pre-cycle to 53% in Cycle I and reached 80% in Cycle II. Teacher activities improved from 70% (high category) in Cycle I to 87.5% (very high category) in Cycle II, while student engagement increased from 55% (high category) to 80% (very high category). These findings demonstrate that the STAD model enhances student learning outcomes and engagement in natural science classes. This study underscores the potential of cooperative learning models to address challenges in elementary science education, particularly in the context of the Fourth Industrial Revolution, by fostering active participation and collaborative skills among students